Using nudging and social marketing techniques to create healthy worksite cafeterias in the Netherlands: intervention development and study design - Elizabeth Velema; Ellis L. Vyth; Ingrid H. M. Steenhuis (BMC, 2017)
Abstract Background The worksite cafeteria is a suitable setting for interventions focusing on changing eating behavior, because a lot of employees visit the worksite cafeteria regularly and a variety of interventions could be implemented there. The aim of this paper is to describe the intervention development and design of the evaluation of an intervention to make the purchase behavior of employees in the worksite cafeteria healthier. The developed intervention called "the worksite cafeteria 2.0" consists of a set of 19 strategies based on theory of nudging and social marketing (marketing mix). The intervention will be evaluated in a real-life setting, that is Dutch worksite cafeterias of different companies and with a number of contract catering organizations. Methods/design The study is a randomized controlled trial (RCT), with 34 Dutch worksite cafeterias randomly allocated to the 12-week intervention or to the control group. Primary outcomes are sales data of selected products groups like sandwiches, salads, snacks and bread topping. Secondary outcomes are satisfaction of employees with the cafeteria and vitality. Discussion When executed, the described RCT will provide better knowledge in the effect of the intervention ﻿"the worksite cafeteria 2.0" on the purchasing behavior of Dutch employees in worksite cafeterias. Trial registration Dutch Trial register: NTR5372 .